(untitled) (Journal of Global Accounting, 2022)
The research intensifies effort at determining whether auditor’s independence has any impact on the audit quality of Nigerian deposit money banks. The study intends to determine the effect of audit fees on the audit quality of Nigeria deposit money banks. The study used Ex-Post Facto research design. A total of thirteen (13) deposit money banks were sampled. Data were taken from the sampled banks’ annual reports and accounts for the years 2010 - 2021. With the help of SPSS version 20.0, simple regression analysis was conducted to test the assumptions. According to the findings, audit fees has a direct but insignificant effect on the audit quality of listed Nigerian deposit money institutions. The researcher therefore recommends that the auditor should be remunerated on the basis of work experience, qualification, duration of the audit assignment, and background profile..